Symmetry of the Magnetoelastic Interaction of Rayleigh and Shear Horizontal Magnetoacoustic Waves in Nickel Thin Films on LiTa O3 - Kuess, M.; Heigl, Michael; Flacke, Luis; Hefele, Andreas; Hoerner, A.; Weiler, Mathias; Albrecht, M.; Wixforth, A. (Physical Review Applied, 2021)
We study the interaction of Rayleigh and shear horizontal surface acoustic waves (SAWs) with spin waves in thin Ni films on a piezoelectric LiTaO3 substrate, which supports both SAW modes simultaneously. Because Rayleigh and shear horizontal modes induce different strain components in the Ni thin films, the symmetries of the magnetoelastic driving fields, of the magnetoelastic response, and of the transmission nonreciprocity differ for both SAW modes. Our experimental findings are well explained by a theoretical model based on a modified Landau-Lifshitz-Gilbert approach. We show that the symmetries of the magnetoelastic response driven by Rayleigh and shear horizontal SAWs complement each other, which makes it possible to excite spin waves for any relative orientation of magnetization and SAW propagation direction and, moreover, can be utilized to characterize surface strain components of unknown acoustic wave modes.
CRIS-Team Scopus Importer:2023-03-27